(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The aim of this research is to determine the availability of diplomatic behavior dimensions among ?administrative leaders, including (protocol rules, etiquette principles, priority among organizational ?levels, compliments supporting organizational objectives, diplomatic language) among the staff of ?Nineveh Governorate Office. The descriptive-analytical approach was adopted to analyze the collected ?data through a questionnaire distributed to a sample of (200) respondents representing the staff of ?Nineveh Governorate Office, which has a total of (400) individuals. The researchers used several ?statistical tools (mean, standard deviation, variance, response rate), and they reached several ?conclusions, including the emergence of a moderately positive trend in adopting diplomatic behavior ?dimensions among administrative leaders at the organizational level under investigation. Additionally, ?they proposed a set of recommendations, including the necessity of linking diplomatic behavior ?dimensions at the organizational level.